KESEHATAN MENTAL SEBAGAI HAK ASASI MANUSIA PADA REMAJA DESA SONGKAR - Rum, Asri Reni Handayani; Nur Arifatus Sholihah; Iga Maliga (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Mental health according to law number 18 of 2014 concerning mental health is a condition in which an individual can develop physically, mentally, spiritually and socially so that the individual is aware of his own abilities, can cope with pressure, can work productively, and is able to make a contribution for the community. Mental health is very important to support the productivity and quality of physical health. Anyone can experience mental or psychiatric disorders. The prevalence of mental emotional disorders as indicated by symptoms of depression and anxiety at the age of 15 years and over reaches around 6.1% of the total population of Indonesia or the equivalent of 11 million people. The purpose of this community service is to increase and develop youth knowledge about mental health as a basic human right. The planned outcoMental health according to law number 18 of 2014 concerning mental health is a condition in which an individual can develop physically, mentally, spiritually and socially so that the individual is aware of his own abilities, can cope with pressure, can work productively, and is able to make a contribution for the community. Mental health is very important to support the productivity and quality of physical health. Anyone can experience mental or psychiatric disorders. The prevalence of mental emotional disorders as indicated by symptoms of depression and anxiety at the age of 15 years and over reaches around 6.1% of the total population of Indonesia or the equivalent of 11 million people. The purpose of this community service is to increase and develop youth knowledge about mental health as a basic human right. The planned outcome is to increase youth knowledge, understanding and awareness of the importance of mental health as a human right. The result achieved is a better understanding and awareness about the importance of mental health for adolescent.me is to increase youth knowledge, understanding and awareness of the importance of mental health as a human right. The result achieved is a better understanding and awareness about the importance of mental health for adolescent.